Pelatihan Deteksi Dini Stunting pada Balita Menggunakan Web-Based Screening Tools Bagi Kader dan Tenaga Kesehatan - Dian Isti Angraini; Anisa Nuraisa Jausal; Wiwi Febriani; Rangga Firdaus; Novita Carolia (Poltekita: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a condition of chronic malnutrition. Efforts to prevent stunting involve many parties, besides government, community participation is also needed, including health workers and health cadres in assessing child growth, development and preventing stunting. The purpose is to train health workers and health cadres to conduct growth, development assessments, early detection of toddlers stunting using web-based screening tools, and to improve nutritional knowledge of toddler mothers. The method used is training in early detection of stunting in using web-based screening tools with the address "modelprestasi.com" through interactive lectures, discussions and practices. This activity was carried out for 1 day at the Sungai Langka Village Hall, Pesawaran Regency, Lampung on Thursday, March 7, 2024 with 50 midwives and cadres as participants. The evaluation results showed that there was an increase in participant understanding of 92% to good, 8% of sufficient, and no participants had a poor understanding of the causes, risk factors, impacts, prevention methods, early detection of toddlers stunting so that they were able to educate and intervene in toddler eating behavior. This activity can improve participants' skills in an effort to improve nutritional knowledge of toddler mothers to monitor toddler growth and development, prevent and overcome stunting